2022
DOI: 10.1021/acs.orglett.2c00319
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Deaminative Allylation of Aliphatic Amines via Dual Cobalt and Organophotoredox Catalysis

Abstract: Despite the rapid progress in C−C bond-forming reactions using Katritzky salts, their deaminative allylation remains a challenge. Inspired by the metallaphotoredox-catalyzed allylic substitution regime, here, we report the deaminative allylation of Katritzky salts via cobalt/organophotoredox dual catalysis. This cross-electrophile coupling enables regioselective allylation using a variety of allylic esters, overcoming the substrate limitations of reported protocols. Mechanistic studies indicate the involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…It is clear that the base therefore prevents charge recombination by deprotonation of the 3 [PC •– :HEH •+ ] intermediate. It is often assumed that the HEH •+ -species is highly acidic and will lose a proton rapidly; here, we show that this is not generally the case, and hence the reason why photoredox catalytic reactions using HEH, or similar reductive quenchers, often require (sub)­stoichiometric amounts of the base to provide productive process turnover. ,, …”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It is clear that the base therefore prevents charge recombination by deprotonation of the 3 [PC •– :HEH •+ ] intermediate. It is often assumed that the HEH •+ -species is highly acidic and will lose a proton rapidly; here, we show that this is not generally the case, and hence the reason why photoredox catalytic reactions using HEH, or similar reductive quenchers, often require (sub)­stoichiometric amounts of the base to provide productive process turnover. ,, …”
Section: Resultsmentioning
confidence: 71%
“…Interest in such processes was initially focused on the combination of nickel or copper catalysis with photoredox catalysis, but recently cobalt has emerged as a potent, alternative metal in dual catalytic procedures. While mechanistic studies for cobalt catalysis have been thoroughly probed under reductive conditions using chemical reductants or via electrochemistry, it remains uncertain whether dual metal/photoredox approaches proceed through the occurrence of similar intermediates. Several features of Co catalysis under reductive conditions remain open for debate, including the intermediacy of either Co I or Co 0 -species ,, and in dual Co/photoredox catalysis, particularly, how the effectiveness of different catalyst components and additives can be rationally optimized.…”
Section: Introductionmentioning
confidence: 99%
“…This regioselectivity is consistent with the previous cobalt/photoredox-catalyzed allylation using nucleophilic radical species, which is likely to proceed via the coupling of a π-allyl Co complex and a carbon radical. 23,32) Control experiments revealed that the cobalt salt (entry 2), the organophotocatalyst (entry 3) and photoirradiation (entry 4) were all required for the reaction to proceed. This is consistent with the proposed mechanism shown in Chart 2.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the recent development of cobalt-catalyzed allylic substitution reactions, [15][16][17][18][19][20][21][22][23] we anticipated that the C-H allylation of N-aryl tetrahydroisoquinolines might be possible without the use of noble-metals via the use of a cobalt/organophotoredox (OPC) dual catalyst system [24][25][26][27][28][29][30] (Chart 1C). The design of the dual catalyst system is shown in Chart 2.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the Earth-abundant first-row transition metals are less expensive and more environmentally friendly than their second- and third-row counterparts. The utilization of these metals, such as copper, 7 nickel, 8 and cobalt, 9–12 in the allylic substitution reactions has attracted growing research interest in recent years, which represents a promising approach for developing more sustainable and cost-effective synthetic methods in this field. 3…”
Section: Introductionmentioning
confidence: 99%